Company Risk, Size, Fiscal Loss Compensation, and Tax Avoidance: Evidence from Indonesian Islamic Companies - Ria Triananda Putri; Ihyaul Ulum; Adi Prasetyo (Journal of Innovation in Business and Economics, 2018)
The purpose of this research is to examine the influence of corporate risk, company size, and compensation tax losses against tax avoidance. Sample was drawn from Jakarta Islamic Index (JII) companies. We use secondary data from Indonesia stock exchange and company’s official websites. PLS-SEM was used to analyze the data, especially we use WarpPLS 6.0. The result indicates that corporate risk and size significantly influence on tax avoidance, while compensation tax losses has no impact on tax avoidance. This means that the higher of corporate risk, the higher amount of tax avoidance. The bigger size of companies, the higher amount of tax avoidance.